The urgent issues of land conservation in Ukraine - O. Malashevska; М. Malashevskyi (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2023)
The article addresses the issue of land conservation at war and post-war reconstruction. The complex understanding of land conservation issues at the current conditions is an important stage of their resolving in the future. The attention is paid to the examination of the issues of the degradation of land as the result of fighting within the scope of the general land degradation factors system. The research is aimed at the structural factor analysis which cause the disturbance, contamination and degradation of land and the determination of the rationalization trends of land use and conservation considering the fighting in Ukraine. The legislation on the disturbed, contaminated and degraded land from the perspective of their utilization has been analyzed.  The key processes causing land contamination, reasons for land degradation, measures on land degradation prevention and reducing its consequences have been singled out. The results can be implemented at the planning of measures on land use and conservation at the current stage and post-war reconstruction, as well as in the future research.